Fusaric acid decreases p53 expression by altering promoter methylation and m6A RNA methylation in human hepatocellular carcinoma (HepG2) cells. Issue 1 (2nd January 2021) - Ghazi, Terisha; Nagiah, Savania; Chuturgoon, Anil A.
ABSTRACT: Fusaric acid (FA) is a food-borne mycotoxin that mediates toxicity with limited information on its epigenetic properties. p53 is a tumour suppressor protein that regulates cell cycle arrest and apoptotic cell death. The expression of p53 is regulated transcriptionally by promoter methylation and post-transcriptionally by N-6-methyladenosine (m6A) RNA methylation. We investigated the effect of FA on p53 expression and its epigenetic regulation via promoter methylation and m6A RNA methylation in human hepatocellular carcinoma (HepG2) cells. HepG2 cells were treated with FA [0, 25, 50, 104, and 150 µg/ml; 24 h] and thereafter, DNA, RNA, and protein was isolated. Promoter methylation and expression of p53 was measured using qPCR and Western blot. RNA immuno-precipitation was used to determine m6A- p53 levels. The expression of m6A methyltransferases ( METTL3 and METTL14 ), demethylases ( FTO and ALKBH5 ), and readers ( YTHDF1-3 and YTHDC2 ) were measured using qPCR. FA induced p53 promoter hypermethylation ( p < 0.0001) and decreased p53 expression ( p < 0.0001). FA decreased m6A- p53 levels ( p < 0.0001) by decreasing METTL3 ( p < 0.0001) and METTL14 ( p < 0.0001); and suppressed expression of YTHDF1 ( p < 0.0001), YTHDF3 ( p < 0.0001), and YTHDC2 ( p < 0.0001) that ultimately reduced p53 translation ( p < 0.0001). Taken together, the data shows that FA epigenetically decreased p53 expression by altering its promoter methylation and m6A RNA methylation in HepG2 cells. This study reveals a mechanism for p53 regulation by FA and provides insight into future therapeutic interventions.